Pengembangan Media Pohon Pintar Untuk Meningkatkan Kognitif Anak Usia 4-5 Tahun: - - Andriani, Ega; Rizqiyani, Revina (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
The purpose of this study is to improve cognition in logical thinking in children aged 4-5 years by developing a valid and interesting smart tree learning media.  This research was conducted at Kindergarten IT Bina Ilmu Sekampung. The subject of this study is 25 students in group A.  This research is included in the type of research research using the ADDIE model which includes: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. The results of validation by validators and product trials show that smart tree media to improve logical thinking skills in children aged 4-5 years is very feasible to use. This was obtained based on the percentages of each, including media experts of 93.75%, material experts of 90.00%, teacher responses of 93.75%, student responses of 90.16%, and all results are included in the Very Feasible category.